Pemanfaatan cangkang biji pala sebagai briket dengan proses pirolisis - Rukmana Rukmana; Suryo Purwono; Ahmad Tawfiequrrahman Yuliansyah (Jurnal Rekayasa Proses, 2015)
The abundance of nutmeg seed shells in Tidore is the reason to study the possibility to produce charcoal briquettes. The use of charcoal briquettes was expected to reduce waste of nutmeg seed shell and can be an alternative energy source with a high economic value. This study aims to investigate the effect of pyrolysis temperature and composition of tapioca adhesive to resulting quality of briquettes. The first step of the research was the preparation of nutmeg seed shells consisted of drying and size reduction into less than 20 mesh size. Afterward, the powder was put into furnace and heated to 350°C, 400°C, and 450°C for 90 minutes. During the process, volume of gas and liquids were measured every 15 minutes, while gas was sampled at 60-minute reaction. When pyrolysis was finished, about 20 g of charcoal was mixed with tapioca adhesive. The compositions of adhesive were 10%, 15%, 20%, 25%, and 30%. Finally, composite was formed in a cylindrical shape and compressed with hydraulic press at f 3 tons weight for a minute. The briquettes were then dried and analyzed with proximate analysis test. The results show that the highest calorific value was 6717.74 cal/g for material pyrolyzed at 450oC and 20% adhesive. The effect of adhesive on shatter index test showed that increasing composition of adhesive makes a better briquette quality as shown by a lower shatter index. In this study, the minimum weight loss was obtained by the addition of 30% adhesive.